Mitigating Distress and Hate: A Rapid School-based Response to the Israeli-Palestinian Conflict in Quebec, Canada - Santavicca, Tara; Vanier Clément, Anabelle; St-Arnaud, Paula; Hassan, Ghayda; Johnson-Lafleur, Janique; Rousseau, Cécile (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2024)
Objectives: Since October 2023, the Israeli-Palestinian conflict has particularly affected international communities and diasporas. Within Quebec, Canada, these tensions added to existing social polarization, not sparing the school environment, by creating feelings of fear, anger, powerlessness, deteriorating school climate, and hindering individuals’ and groups’ ability to empathize with one another. This article reports a rapid intervention aimed at mitigating distress and hate in the educational environment through training and supporting school teams.Methods: Five training webinars were organized for school professionals within the Quebec Ministry of Education. Pre-webinar surveys were disseminated to participants to identify if and how the conflict had impacted their school environment to inform trainings. A thematic analysis was carried out on pre-webinar survey responses, chat feedback and field notes collected throughout the webinars.Results: Having an opportunity to share and address concerns, receive reassurance, positive reinforcement, and guidance around strategies, proved to be helpful for school teams. In a context of crisis and politicized emotions, the intervention legitimized a range of emotional responses, addressed school team and community divides, and encouraged double empathy while acknowledging its limits. Finally, these activities also unveiled the potential dangers associated with silencing dissent and highlighted the value of mobilizing agency around school teams’ common mandate to educate and protect children from all communities, and in spite of the expression of divergent solidarities.Implications: In times of crisis, school team and youth engagement in empathy-based activities facilitating non-judgmental expression and awareness of the Other can appease heightened emotions and prepare for dialogue, healing, and coexistence as a way forward.